Linguistic document research technologies (forensic and procedural aspects) - Petrova, Iryna; Sezonov, Viktor; Perlin, Stanislav; Sezonova, Olga; Piddybna, Alina (Linguistics and Culture Review, 2021)
Linguistic examination is a modern type of forensic examination, which is directly related to the study of the products of speech activity in order to establish facts (circumstances) of evidentiary significance in a particular (criminal, civil and administrative) case. Although linguistic knowledge is often useful, author identification has not yet reached a significant level of reliability. The main purpose of the study is to investigate the current state of legal regulation of document linguistic examination in Ukraine and to disclose the criminal and procedural aspects of linguistic technologies of document examination. The research process involved using a combination of general scientific, philosophical and specialised scientific methods, which are in line with the aims and objectives set by the authors. The philosophical basis of the methodological paradigm of the study is the dialectic as a philosophical learning method. The author’s conclusion provided a conceptual understanding of the implementation of document linguistic examination in Ukraine.